Rhenium and Osmium in Some Canadian Ores by Neutron Activation Analysis - Schindler, Norman John (My University, 1975)
Neutron activation analysis procedures have been developed for the determination of rhenium and osmium in common metallic minerals from wide variety of ore deposits. The Os method is based on double distillation, solvent extraction and precipitation of the metal. The Re method uses double anion exchange, solvent extraction and precipitation. The accuracy of the methods were checked against molybdenite and Cu-Ni matte standards. A literature survey of the rhenium and osmium is presented and the geology of the deposits is presented. The analytical results are discussed in terms of the current feasibility of dating ores by the Re-Os method, and their geological significance.
Keywords: Geology; Geology